COACTION EFFECT OF NEW PYRAZOLE-CONTAINING BISPHOSPHONATES AND VITAMIN D3 IN EXPERIMENTAL OSTEOPOROSIS - VELIKY, M.; LABUDZYNSKYI, D.; LISAKOVSKA, O.; PASICHNA, E.; IVONIN, S. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Bisphosphonates remain one of the most effective drugs to treat diseases of the musculoskeletal system. Among a wide range of possible options, the methods of bioinformatic analysis were developed, selected and synthesized analogs of bisphosphonates, the radical of which were selected pyrazole derivatives. The development of new advanced bisphosphonate analogues has broad prospects for medical application. The study is devoted to the investigation of the combined action of synthesized nitrogen-containing bisphosphonates (pyrazole-containing analogues) and vitamin D3 in the correction of mineral metabolism disturbances in osteoporosis. The work was performed on a rat model of alimentary osteoporosis, which was characterized by the development of hypocalcemia, hypophosphatemia, decreased serum 25OHD concentration and severe bone tissue demineralization. New pyrazole-containing bisphosphonates inhibited the process of bone demineralization (resorption) and improved mineral metabolism in rats with alimentary osteoporosis with varying efficiency. The action of the investigated substances resulted in an increase in the concentration of calcium, inorganic phosphate and a decrease in the activity of alkaline phosphatase and its isoenzymes in the serum. The ash content, calcium and phosphorus level in the ash of the tibia was increased as well, along with improving osteometric characteristics of the tibia (length and thickness of the proximal epimetaphysis). The combination of pyrazole-containing bisphosphonates and vitamin D3, which normalizes the concentration of 25OHD in the serum and provides the synthesis of biologically active, hydroxylated form of cholecalciferol, has been more effective in the correction of mineral metabolism impairments in rats with alimentary osteoporosis. According to the experimental results, the combination of vitamin D3 with bisphosphonate ISP-30, as a substance with the highest biological efficiency in regulating bone remodeling, enhancing osteogenesis and inhibition of resorption, is the most promising for further research.